New language of qualitative method - Gubrium Jaber F; Holstein James A (New York OUP, 1997)
The book examines alternate vocabularies for conveying social reality. It offers a new theoretical view which reintegrates the traditional emphasis on the whats of social life with a contemporary understanding of the hows and whys. The text considers the
Keywords: Social sciences-research-methodology